ผลกระทบต่อกระบวนการดูดซึมยาทางช่องว่างระหว่างเซลล์จากพืชสมุนไพรที่มีฤทธิ์ต้านเบาหวานในพื้นที่ของโครงการอนุรักษ์พันธุกรรมพืชอันเนื่องจากพระราชดำริฯ : รายงานผลการดำเนินงาน - สุรีย์ เจียรณ์มงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this study was to investigate and compare the effects of 4 herbal plants in the Plant Genetic Conservation Project area under The Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn on the paracellular transport pathway, using the in vitro model of the Caco-2 cells. The plants were selected into this study by its ability to inhibit -glucosidase, which is a drug target for diabetic control. These plants included Pterospermum littorale Craib (Family Sterculiaceae); Dialium cochinchinense Pierre (Family Fabaceae); Mamecylon plebejum Kurz. var. ellipsoideum Craib. (Family Melastomataceae) and Thespesia populnea (L.) Soland.ex Corr. (Family Malvaceae). The restrictive integrity of Caco2 monolayers was assessed by transepithelial electrical resistant (TEER) values and Lucifer yellow transport. The results demonstrated that all of the plant extracts at the highest concentration in this study had no disruptive effect on the integrity and restrictive barrier property of the Caco-2 monolayers. The findings suggested that these extracts would not affect the tight junction integrity. Thus, they would be unable to facilitate the paracellular transport pathway